Kegiatan Berbasis Pendidikan Sebagai Upaya Khidmah Kepada Masyarakat Di Desa Sumokali - Nadziyah Shofiroh; Lily Oktavia; Fahriyatul Usnania; Fikriyah Hanim; Fifi Lathifa; Fahrur; Muhammad Mukhlis; Mariska Ayu Lestari (LPPM, STAI Al-Azhar Menganti, 2022)
Community service in the field of education is one of the UNUSIDA real work college student work programs in Sumokali village, Candi district, Sidoarjo regency. Real Work Lecture (KKN) is a means to implement the Tri Dharma of Higher Education, the contents of the Tri Dharma of Higher Education are three points, Education and Teaching, Research and Development, and community service. Through community service activities in Sumokali village, there is a synergy between college students and the community as a form of democratic knowledge. The method used in the learning mentoring program is by providing exclusive learning process assistance and providing fun learning methods, for example by presenting material through songs, games, and so on. The purpose of this service is to provide an understanding to the surrounding community of the importance of education as an effort to educate the nation's children and increase student interest in learning at SDN Sumokali and MI Sumokali with fun teaching. The form of devotion is carried out through teaching activities at SDN Sumokali, MINU Sumokali, and tutoring activities